Microbes and Their Role in Food Sciences - Bilal, Muhammad; Ibrahim, Awais; Saleem, Rabbia; Husnain, Muhammad; Alam, Hafiz Munsif; Mazhar, Maham Ghafoor; Ahmed, Umair; Shahbaz, Muhammad; Mughal, Zain Ul Abideen; Mushtaq, Hafsa (Indus Journal of Bioscience Research, 2025)
Microbes are crucial to food science because they have an impact on numerous characteristics of food manufacturing, preservation and safety. In order to produce a varied choice of food products, including bread, dairy, pickled foods and alcohol, the fermentation and other processes require the help of beneficial microbes like yeast, bacteria and molds. These microorganisms also affect the development of food's flavors, textures and nutritional value. Bacteria also help in food preservation by extending their shelf life, maintaining food safety and preventing the development of harmful diseases. While the presence of harmful microorganisms such as molds and pathogenic bacteria can lead to contamination, spoiling and foodborne illnesses, advances in genetic engineering and biotechnology have improved product quality and safety by providing more precise control over microbial activity in food production. Despite these benefits, concerns about microbial resistance, environmental impacts and the ethics of altering microbial ecosystems persist. Microorganisms are abundant in soil, water, air, food, and the digestive tracts of humans and animals. They play a vital role in food production, safety, storage, preservation, and processing. Microbes such as bacteria, yeasts, and molds are used to produce foods like wine, dairy, and baked goods. However, contamination can occur at any stage—growing, harvesting, transport, storage, or preparation. Uncontrolled microbial growth in food can lead to visible spoilage signs, including color changes, powdery growths, altered taste and smell, and surface effervescence, compromising the food’s quality and safety. Thus, microbial control is essential in the food industry.